IMPLEMENTASI HUKUM DALAM PERSFEKTIF PERILAKU MASYARAKAT - Azmi Sirajuddin (Istinbath : Jurnal Hukum, 2017)
Abstract Implementation of law is the most useful for a nation and a state in a country thas has powerfull of protecting its people to do better and the best in their attitudes and behaviors when they live and do everything in order to have good connection among society in the social climate. Having understood in law is one thing to do every action based on the law either God’s law or state’s law. The functions of law are to control the human’action, to change the situation to better situation and to give justice and prosperious for people in a country. No one to disturb and make noisy till one has good condition by obeying law that is created by God and Human (Indonesian Legislative Assembly in Indonesian Contects). By knowing and obeying law, person will get safety when they go and live. Law means regulations that manage human to surrender to that law that is created by God and Human (state). In Islamic law, law is consist of five principles, wajib (compulsory), not allowed (haram), allowed (sunnah), hate (makruh), and mubah. All those fungtions of the law always protect us/human from demage, poverty, and crime. Law is as a soul for every human and too law is as a foundation for a country to protect its people from demage, povery, and crime. Law gives freedom to do by the condition obey to the law. Who breaks the law must be funished either by low funishment or hard funishment till go to a jail to be responsible what they have done. Key word: Implementation, law, persfektive, human’s behaviors in society